Politik Hukum Agraria Pada Tanah Ulayat - I Nyoman Prabu Buana Rumiartha (Jurnal Aktual Justice, 2019)
The responsive character of Law Number 5 of 1960 concerning Basic Regulations on the Principles of Agrarian Law is reflected in the norms contained in Article 5. The politics of agrarian law on customary land also refers to Article 18B paragraph (2) of the 1945 Constitution which emphasizes: "The state recognizes and respect indigenous peoples and their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia as regulated in law ". The above constitutional guarantees can then be traced in the UUPA, particularly in Article 5 of the UUPA which states that national agrarian law is based on customary law. This means that the legal strength of land rights for customary communities is highly guaranteed in Indonesia's positive law. That the control of ulayat / customary land is not regulated in writing but it is felt in the mind of each member of the customary law community, besides that the customary law community has historically been founded in philosophy before the birth of the Indonesian State.